Sociology of childhood, children participation and peer culture: mapping academic production on the theme - Flávia Franzini Dip; Gabriela Guarnieri de Campos Tebet (Universidade Federal de Santa Catarina, 2019)
The main reason for this work was understand in Sociology of childhood, how the concepts of peer culture and children participation have been understood. We seek to understand which ways have been followed to understand the child as a social actor and the way they have been developing themselves as builders of their own culture and participating in their own life. For that it was used bibliographic research of foreign and Brazilian authors that talk about the subject and also having the website Scielo as an important data source. We analyse data and articles published between 1994 and 2016 and we understand that peer culture is a series of activity, routine, values produced by a group of children in interaction of other children and playing together, and children participation is only possible when relations between adults and children are set, able to promote or make it harder the children's participation. The highlight from the data source and analysed articles is that we need to change the conception of the adult as a superior and the child the inferior. It is also important that we create spaces where children can be part of decisions made in group.